How to measure attitudes - Henerson,Marlene. E.; Morris, Lynn Lyons; Fitz-Gibbon, Carol Taylor (New Delhi : Sage publications, 1987)
This book aims to develop basic skills in designing and using instruments for the measurement of attitudes and wherever possible, recommends procedures, rules of thumb and practical strategies for performing evaluation tasks related to the assessment of peoples' attitudes.
Includes bibliographical references and index.
Keywords: Attitude (Psychology) -- Testing; Psychological Tests